Science and Civilisation in China. Vol. 1 Introductory Orientations - Needham, Joseph (Cambridge University Press, 1956)
Dr Joseph Needham's account of the Chinese achievement in science and technology will stand as one of the great works of our time. It has be en acclaimed by specialists in both East and West and also by readers with wider and more general interests. The text, based on research of a high critical quality, is supported by many hundreds of illustration s and is imbued with a warm appreciation of China. Volume I is an intr oductory volume, in which Dr Needham prepares his readers for the stud y of a whole human culture. He begins by examining the structure of th e Chinese language; he reviews the geography of China and the long his tory of its people, and discusses the scientific contacts which have o ccurred throughout the centuries, between Europe and East Asia.